Effect of poly (methyl methacrylate)-grafted-talc content on mechanical properties and thermal degradation of poly (vinyl chloride) composites - Hassan, Azman (2012)
The influence of talc and poly (methyl methacrylate) (PMMA)-grafted (g)-talc on the mechanical properties of poly (vinyl chloride) (PVC) was investigated. The graft copolymerization was carried out under nitrogen atmosphere, using the free radical initiation technique. The blend formulations were first dry blended using a mixer before being milled into sheets on a two-roll mill at 165°C, and then hot pressed into composites at 190°C. The flexural modulus of both composites increased with increasing filler content from 0 to 20 part per hundred resin (phr), however the increment of grafted (57.7%) was higher than ungrafted composites (48.5%). A similar trend has also been observed for thermal stability. The impact strength of grafted was increased by 45.82%, whereas 18.96% in reduction was observed for the ungrafted composites. The decrement of flexural strength by 16.6% and 21.1% of grafted and ungrafted, respectively, has also shown the improvement in mechanical properties of grafted composites.